The usage of photoelectric modules in the outdoor lighting system of university building; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Tsybikov B. B. Bator (2017, 2017)
Title screen